The association between level IV/V metastasis and the recurrence, distant metastasis, and survival outcomes in hypopharyngeal squamous cell carcinoma - Ruichen Li; Qi Wang; Siyuan Ma; Ji Li; Yang Zhao; Xiaoshen Wang (Therapeutic Advances in Medical Oncology)
Background: The presence of level IV/V metastasis is a significant prognostic factor for patients with oral and oropharyngeal cancer, while level IV lymphadenopathy defines the N3 stage in nasopharyngeal carcinoma. However, the current staging system for hypopharyngeal squamous cell carcinoma (HPSCC) does not consider the location of involved nodes. Objectives: To evaluate the risk factors and prognostic impact of level IV/V metastasis in patients with HPSCC. Methods: The analysis included 2740 HPSCC patients from the SEER (Surveillance, Epidemiology, and End Results) database, followed by a validated study on 232 patients with pathologically positive nodes (pN+) at our center. Results: Of the 2740 patients, 1961 presented with metastatic lymph nodes (LNs), 20.8% and 14.1% had nodal involvement in level IV and level V, respectively. Multivariate analysis revealed that N3 and M1 stages were independently associated with level IV/V metastasis. Level IV metastasis was the sole independent adverse factor for overall survival (OS) among all LN regions ( p  < 0.05). Regarding cancer-specific survival (CSS), only level IV and V involvement were independent predictors of prognosis ( p  < 0.05). The rate of pN+ at levels IV and V in our center was 35.8% and 16.4%, respectively. The advanced pN stage was independently associated with metastasis to level IV or V. Patients with level IV/V metastasis had significantly higher rates of regional recurrence and distant metastases ( p  < 0.001). Multivariate analysis confirmed a significant association regarding OS, CSS, locoregional relapse-free survival (LRFS), or distant metastasis-free survival between patients with and without level IV metastasis ( p  < 0.05). Patients with level IV/V disease exhibited decreased survival rates across stages pN1 to pN3. Postoperative chemoradiotherapy improved LRFS in patients with level IV lymphadenopathy and OS/CSS in patients with level V metastasis. Conclusion: Metastasis to level IV/V was associated with a worse prognosis in HPSCC patients. The level IV/V should be considered for future improvements to the staging system. Design: A retrospective study.